Theoretical investigation of the Diels-Alder reactions of unsaturated boronates - Pellegrinet, Silvina Carla (2013)
The Diels-Alder reactions of simple unsaturated boronates have been investigated using computational methods and the results were compared with those for the analogue dihalo- and dialkylboranes. Our results indicate that the activating effect of the boronate moiety is small. All the studied reactions are concerted normal electron-demand Diels-Alder reactions with asynchronous transition structures and weak [4 + 3] C-B secondary orbital interactions, which explains the low experimental reactivity. Both electronic and steric effects contribute to give the observed low stereo- and regioselectivities.